Home Automation System using Raspberry Pi - Gaudani, Hetal; Vora, Saurabh; Todarmal, Swati (IJRDO -Journal of Computer Science Engineering, 2015)
Nowadays automation encompasses many vital elements,systems and job functions. To embed this term with controllingdevices especially for electric devices at home will give a system whichwill turn to be highly beneficial to end user. Therefore we havepresented the architecture and implementation of the homeautomation system for controlling electric devices using raspberry pias the central (main) hardware. The proposed system is having twoparts; the first part consist web server controlling user interface andthe details of the devices are stored in the database. While second partconsists hardware structure which provides appropriate interface toraspberry pi and electric devices. This part also consist a controllermodule as a bridge between raspberry pi and electric devices. Unlikemost of other available home automation system we have usedraspberry pi as the main hardware due to benefits like low cost, highperformance and massively diverse range of uses and applications